Influência dos fatores maternos no período de manifestação da restrição de crescimento fetal em uma maternidade de referência em Fortaleza - Moniz, Cesaltina Soares (2021)
To evaluate the influence of maternal factors in the period of manifestation of fetal growth restriction and neonatal outcome at Maternity School Assis Chateaubriand. This paper is a descriptive, observational, retrospective study with 134 cases of pregnant women who developed fetal growth restriction attended between January 2018 to April 2019. The data was collected from newborns alive, who weighted less than 2700 grams, accordingly to the records of the infant record book at the neonatology room. The data were organized in a document with the software Microsoft Office Excel 2007 and the variables evaluated by the Pearson and t-student tests of the STATA 11 statistical program, chi-square test and P <0.05 were considered statistically significant. Growth restriction was divided into groups: according to the time of diagnosis (group A late, group B early); according to the time of resolution (group C at term, group D preterm); according to resolution stage (group E stages I, group F stages II, III and IV). The average maternal age was 28 years, and in it’s majority nulliparous 69 (51.5%). The diagnosis was made at around 34 weeks and pregnancy resolved at 35 weeks. Overweight at the beginning of pregnancy and increased blood pressure, were revealed to be the most common maternal characteristics. Early FGR and premature delivery were influenced by advanced maternal age and high blood pressure. Stage I predominated in both early and late forms and the most severe stages were associated with early Fetal Growth Restriction (14.8%). The greatest neonatal complications were related to the resolution of pregnancy in more advanced stages of the disease, and the early form contributed to the fact that the weight and height of newborn babies were extremely lower compared to a late FGR. The worst developments were to the early form, related to extended periods of hospitalization (9.5/26.1) and neonatal death (00/18.5%). Primigravidae are at a higher risk of progressing to FGR, aggravated by their higher maternal age and high blood pressure. The majority evolves to premature birth with worse neonatal outcomes for those born at the most advanced stage of the disease.